2021
DOI: 10.1007/s11666-021-01271-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Gradients Govern Impact Dynamics in Thermoplastic Polymer Cold Spray

Abstract: Most reports simulating in-flight particle temperatures in polymer cold spray ignore intra-particle thermal gradients that develop in-flight, and, to date, no research group has simulated the effects of thermal gradients on polymer particle impact dynamics. This report investigates the effects of intra-particle thermal gradients on the impact response of thermoplastics, using properties of polyether-ether-ketone (PEEK) in a simulated like-onlike cold spray deposition process. Particle velocities and internal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Particle temperature and velocity upon impact with the substrate were simulated using the one-dimensional (1D) methodology outlined in Bacha et al 39 The nozzle was modeled as a simple converging-diverging conical geometry with a side inlet for the powder feed. The side inlet was assumed to not affect the main gas flow.…”
Section: Modeling Of Particle Flightmentioning
confidence: 99%
See 2 more Smart Citations
“…Particle temperature and velocity upon impact with the substrate were simulated using the one-dimensional (1D) methodology outlined in Bacha et al 39 The nozzle was modeled as a simple converging-diverging conical geometry with a side inlet for the powder feed. The side inlet was assumed to not affect the main gas flow.…”
Section: Modeling Of Particle Flightmentioning
confidence: 99%
“…The model development details are beyond the scope of the present study and are therefore excluded for brevity. However, complete details regarding the particle flight model can be found in Bacha et al…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…A thermal gradient exists within the particle and generally leads to a gradient of thermal properties. In the case of polymer particles, several authors [16,17,29,30] highlighted the importance of this thermal gradient for a better understanding of polymer coating by the cold spray process.…”
Section: Evolution Of the Particle Temperature: Analytical Approachmentioning
confidence: 99%
“…Bacha et al [17] investigated the impact behavior of polyether ether ketone (PEEK) particles considering different thermal gradients for the particle. They showed that important shear stresses occur in the localized high-temperature regions.…”
Section: Introductionmentioning
confidence: 99%